Standard Agreements: Review of the Principles Pacta Sunt Servanda, Good Faith and Fairness (Lex Scientia Law Review, 2025)
The use of standardized contracts today shows one side of the dominance of the modern economy by business entities or companies and even banks. Agreement is one of the main sources in civil law relationships, where the parties involved have the freedom to determine the contents and form of the agreement in accordance with Article 1338 of the Civil Code. In practice, this freedom often does not take place in a balanced manner, especially in standardized agreements. This research focuses on the principle of justice in standard agreements, where the agreement should be able to fulfill a sense of justice for the parties.    Justice is very important in standard agreements, to avoid exploitative practices and ensure equal legal protection between the parties. Based on this narrative, it is important to examine how the principle of justice is applied, protected, and enforced in standard agreements that develop in the community. The approach used in this study is normative juridical, focusing on secondary data. The results of the study show that the application of the fairness aspect of contracting in agreements or standardized contracts is still far from expectations. Agreements made in standardized forms tend to benefit one party who has a stronger bargaining position, who usually acts as the "designer" of the standardized contract.